Indexicality of won: Yoruba language and culture - Agwuele, Augustine (Journal of African cultural studies, 2012)
The Yoruba pronoun won is equivalent to the English pronoun they, and can occur in various syntactical constructions including passives. Indefinite pronouns of passive constructions by definition are silent about the identity of their subject. However, Yoruba peoples' cultural interpretation attributes definiteness, concreteness, and agency to the indefinite pronoun won in specific usages. Based on the study of utterances obtained from popular, contemporary usages, and individual narratives all featuring the passivized pronoun won, this article examines Yoruba habitual practices. It argues that understanding the cultural meaning of won is invaluable for understanding the Yoruba peoples' habitual view of causality in addition to the way it guides their interpersonal interactions. Further, won is shown to index a certain Yoruba worldview and to guide their efforts to achieve their presumed goals of earthly existence. The article does four things: (1) it explicates the content of the pronoun won, exemplifying its various manifestations in contemporary popular Yoruba usages; (2) it shows the spiritual foundation of won; (3) it provides evidence to argue for its cultural continuity in spite of modernity and western/eastern religious traditions; and (4) it discusses its place in the socio-political continuity and identity formation of Yoruba peoples. [PUBLICATION ABSTRACT]